1998
DOI: 10.1074/jbc.273.29.18235
|View full text |Cite
|
Sign up to set email alerts
|

Splice Variants of the Drosophila PS2 Integrins Differentially Interact with RGD-containing Fragments of the Extracellular Proteins Tiggrin, Ten-m, and D-Laminin α2

Abstract: Two new potential ligands of the Drosophila PS2 integrins have been characterized by functional interaction in cell culture. These potential ligands are a new Drosophila laminin ␣2 chain encoded by the wing blister locus and Ten-m, an extracellular protein known to be involved in embryonic pattern formation. As with previously identified PS2 ligands, both contain RGD sequences, and RGD-containing fragments of these two proteins (DLAM-RGD and TENM-RGD) can support PS2 integrin-mediated cell spreading. In all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 53 publications
2
61
0
4
Order By: Relevance
“…These results suggest that PGANT3 may glycosylate a subset of basal ECM proteins (including tiggrin) in the developing wing disc. The aforementioned ECM proteins are also known to specifically interact with ␣PS2 integrin to mediate cell adhesion in a number of developmental contexts (9,10,13,14). We postulate that glycosylation of ECM proteins in addition to tiggrin could also play a role in the wing blade adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PGANT3 may glycosylate a subset of basal ECM proteins (including tiggrin) in the developing wing disc. The aforementioned ECM proteins are also known to specifically interact with ␣PS2 integrin to mediate cell adhesion in a number of developmental contexts (9,10,13,14). We postulate that glycosylation of ECM proteins in addition to tiggrin could also play a role in the wing blade adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…For all cell culture experiments, the ␣PS2C (canonical) and ␤PS4A isoforms were used (Graner et al, 1998). In some experiments, these integrin-expressing S2/M3 cells also stably expressed Drosophila talin head-GFP chimeras (wild-type or R367A mutants) under the control of the yeast Gal4 UAS .…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…We have previously shown that an ECM protein, Tiggrin (3,18,19), is normally modified by the post-translational addition of the sugar GalNAc (20) through the action of a member of the UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferase family of glycosyltranferases (EC 2.4.1.41). This type of evolutionarily conserved protein modification, known as mucin-type O-glycosylation (21)(22)(23), was shown to be required for proper cell adhesion between the epithelial cell layers comprising the Drosophila wing blade.…”
mentioning
confidence: 99%